Validation of treatment strategies for enterohaemorrhagic Escherichia coli O104:H4 induced haemolytic uraemic syndrome: Case-control study - Menne, Jan; Nitschke, Martin; Stingele, Robert; Abu-Tair, Mariam; Beneke, Jan; Bramstedt, Joern; Bremer, Jan P.; Brunkhorst, Reinhard; Busch, Veit; Dengler, Reinhard; Deuschl, Guenther; Fellermann, Klaus; et al. (British Medical Journal, 2012)
Objective: To evaluate the effect of different treatment strategies on enterohaemorrhagic Escherichia coli O104:H4 induced haemolytic uraemic syndrome. Design: Multicentre retrospective case-control study. Setting: 23 hospitals in northern Germany. Participants: 298 adults with enterohaemorrhagic E coli induced haemolytic uraemic syndrome. Main outcome measures: Dialysis, seizures, mechanical ventilation, abdominal surgery owing to perforation of the bowel or bowel necrosis, and death. Results: 160 of the 298 patients (54%) temporarily required dialysis, with only three needing treatment long term. 37 patients (12%) had seizures, 54 (18%) required mechanical ventilation, and 12 (4%) died. No clear benefit was found from use of plasmapheresis or plasmapheresis with glucocorticoids. 67 of the patients were treated with eculizumab, a monoclonal antibody directed against the complement cascade. No short term benefit was detected that could be attributed to this treatment. 52 patients in one centre that used a strategy of aggressive treatment with combined antibiotics had fewer seizures (2% v 15%, P=0.03), fewer deaths (0% v 5%, p=0.029), required no abdominal surgery, and excreted E coli for a shorter duration. Conclusions: Enterohaemorrhagic E coli induced haemolytic uraemic syndrome is a severe self limiting acute condition. Our findings question the benefit of eculizumab and of plasmapheresis with or without glucocorticoids. Patients with established haemolytic uraemic syndrome seemed to benefit from antibiotic treatment and this should be investigated in a controlled trial.
CRIS-Team Scopus Importer:2020-11-12